Data driven : how performance analytics delivers extraordinary sales results - Dearborn, Jenny (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Data Driven is a uniquely practical guide to increasing sales success, using the power of data analytics. Written by one of the world's leading authorities on the topic, this book shows you how to transform the corporate sales function by leveraging big data into better decision-making, more informed strategy, and increased effectiveness throughout the organization.
Chapter 2: Pulling Back the CurtainNotes; Chapter 3: Changing Mindsets; Notes; Chapter 4: Finding the Keys; Notes; Chapter 5: Describing What Happened; Notes; Chapter 6: Diagnosing What's Wrong; Chapter 7: Predicting What's Ahead; Chapter 8: Prescribing What to Do; Chapter 9: Celebrating Success; About the Author; Index; End User License Agreement.
Includes index.
Print version record.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Sales management; Selling; Marketing; Marketing; Ventes -- Gestion; Vente; Marketing; selling; marketing; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Marketing; Sales management; Selling